Post CO VID-19 Encephalopathy Treatment - Jinna I. Lebedeva; Tatyana I. Kutergina; Elena F. Turovinina; Irina V. Elfimova; Alexandra S. Orlova (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2021)
Aim. To evaluate the severity of encephalopathy and the efficacy of the second stage of rehabilitation in patients with post-infectious encephalopathy. Material and methods. The study included 92 patients with post-infectious encephalopathy, who underwent the second stage of rehabilitation after СOVID-19 infection. All patients were divided into 2 groups: those, who were referred to rehabilitation after the end of the treatment (n=54) and those, who refused to undergo rehabilitation (n=38). In all cases the severity of coronavirus infection, percentage of pulmonary involvement (based on chest CT-findings) and the presence of comorbid pathology were assessed. The severity of the prevailing syndromes was assessed using the International Classification of Functioning, Disability and Health (ICF). Patient status dynamics was assessed using Rehabilitation routing scale (RRS), Rivermead, Holden and Hauser scales. Results and discussion. Post-infectious encephalopathy was mainly accompanied by vestibular ataxia syndrome in 51 (55.4%) patients (in 51.9% and 60.5% patients in groups 1 and 2, respectively) and cerebro-asthenic syndrome in 73 (79.3%) patients (in 72.2% and 89.5% patients in groups 1 and 2, respectively). Comprehensive rehabilitation process is characterized by staging aimed at compensating for all components of pathogenesis that affected during the period of severe course of COVID-19 infection. Rehabilitation was an effective measure for the compensation of neurologic complications of COVID-19 infection. After 2 weeks, cerebro-asthenic syndrome was observed in 24.1% patients in group 1 and 71.0% in group 2 (p <0.05), vestibular ataxia syndrome - in 18.5% and 28.9% (p<0.05) of patients in groups 1 and 2, respectively. The current pandemic is highly likely to be accompanied by a significant increase in the prevalence of encephalopathy affecting the ability to return to daily functioning. Conclusion. The main manifestations of post-covid encephalopathy are cerebro-asthenic (79.3%) and vestibular ataxia (55.4%) syndromes. Therapeutic and rehabilitation measures carried out at the 2nd stage of rehabilitation is an effective measure to compensate for the severity of post-covid encephalopathy.